El rol de los ambientes semi-naturales en la abundancia y diversidad de coleópteros edáficos en los viñedos de la Costa de Berisso, Argentina - Paleologos, María Fernanda (2015)
Semi-natural environments surrounding the cultivated crops ensure maintenance of ecological functions.\nHowever, increasing the diversity within the crop plots would also contribute to enhance ecological functions in the agroecosystem. The influence of semi-natural habitats on abundance, richness, and diversity of Coleoptera, as well as on the dominance of different functional groups (predators, detritivores, phytophages) was evaluated.\nThis study has been carried out in two vineyards with different structure and composition in groundcover, the socalled “old” lowland vineyards and “new” highland vineyards. Coleopterans were sampled using Pitfall traps.\nTwenty-four coleopteran families in the old and 23 in the new were identified. The degree of importance of seminatural environments was markedly different between regions. In old vineyard, the beetles abundance and the abundance of trophic guilds was higher in the vineyard crop than in semi-natural environments. In the new ones were greater in semi-natural environments. Our results show that the role of semi-natural habitats, to favor the presence of fauna, depends of their environmental characteristics, and of the diversity within crop plots.